Harvest of Red-Legged Partridge in Central Spain. (The Journal of wildlife management, 2012)
A basic rule to attain sustainable use of harvested resources is to adjust take to availability. Populations of red-legged partridges in Spain have decreased in recent decades, and releases of farm-bred partridges to improve short-term availability are increasingly common. We used questionnaires and bird surveys to assess whether harvest was related to availability of wild partridges or intensity of farm-bred partridge releases. We studied 50 hunting estates, including 6 administratively labeled as intensive (with few numerical and temporal restrictions to releases). In addition, we considered hunting pressure (number of hunters × hunting days/km(2)) and habitat as explanatory variables in the analyses. In intensive estates, annual harvest was exclusively related to release intensity, indicating that in these estates hunting is detached from natural resources and approaches an industrial activity based on external inputs. In non-intensive estates, harvest was affected by wild stock availability, walked-up shooting pressure, and habitat (greater harvest in estates with more Mediterranean shrubland). In these estates, releases did not increase annual harvest, and can be considered an inefficient practice. Additionally, the relationship between abundance estimates and harvest disappeared in estates with low partridge abundance estimates, suggesting possibilities for overharvesting in a large proportion of estates. Increasing the abundance of wild red-legged partridge through techniques like habitat management, and improving the adjustment of harvest to availability, may be a good strategy to increase long-term harvest in non-intensive estates. Additionally, Government and managers must create ways to segregate and label the estates where only wild red-legged partridges are managed from those where releases are used, to reduce ecological costs of management decisions. © 2012 The Wildlife Society.